Analisis Manajemen Risiko Teknologi Informasi Menggunakan Framework ISO 31000:2018 - Devara Liko Ivander; Frederik Samuel Papilaya (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Information Technology is an innovation encompassing artifacts, techniques, and knowledge that can solve human problems. However, its utilization must be accompanied by a thorough understanding to prevent various risks that could adversely affect multiple parties. PT XYZ Bawen Branch is a manufacturing company specializing in cardboard box and cardboard sheet packaging, established since 1995 and situated in the Bawen Subdistrict, Semarang Regency, Central Java. PT XYZ has incorporated IT/IS in its business processes, where IT/IS can enhance operational efficiency. Nonetheless, it's important to note that the implementation of IT/IS doesn't always proceed seamlessly and inherently carries its own shortcomings. Hence, this study aims to identify, assess, and mitigate the existing risks within PT XYZ using the ISO 31000:2018 framework. From this research, 26 potential risks were identified within the company. Out of these, there are 15 risks classified as low-risk, 5 as medium-risk, 5 as medium-high-risk, and 1 as high-risk. Among the discovered risks, the researchers offer suggestions or recommendations for risk management, enabling the company to minimize the identified risks and reap the benefits of this research, aligning with the research objectives. Companies need to carefully assess and address risks associated with technology adoption to ensure the smooth functioning of their business processes and to safeguard against any adverse outcomes